ANALISIS YURIDIS PEMBUBARAN ORGANISASI KEMASYARAKATAN (ORMAS) BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2013 TENTANG ORGANISASI KEMASYARAKATAN - hasri, Gio irwana; Kasman Siburian; Hisar Siregar (Nommensen Journal of Legal Opinion, 2024)
Community Organizations are community associations that form organizations with an orderly nature and structure, usually starting from the highest/central level to the lowest level/leadership at the regional level or even community associations. Considering that social organizations provide freedom of association, assembly and expression of opinion as a form of guarantee of human rights. Therefore, the reasons used are based on statutory regulations as explained in Article 60 paragraph (1) and paragraph (2) Government Regulations in Lieu of Law of the Republic of Indonesia Number 2 of 2017 concerning Amendments to Law Number 17 of 2013 concerning Organizations Even though Community Organizations can be dissolved, the dissolution procedure must be carried out democratically. The government must not monopolize the authority to disband a mass organization by negating the role of other state institutions, so that the government will tend to behave authoritarian. The consequence of an authoritarian government is that the laws that are born will be repressive in nature, prioritizing the interests of the rulers over the people. This research is included in Normative Juridical research, namely research that examines legal norms that originate from legal rules, namely laws. The conclusion obtained in this research is that the system for dissolving mass organizations in Indonesia still does not have clear indicators and mechanisms that are in accordance with the existence of the rule of law. The dissolution of mass organizations is based on the mass organization not carrying out its obligations and prohibitions. So the reasons for disbanding mass organizations can be classified into threats to democracy, national ideology, constitution, state sovereignty and national security. The mechanism for dissolving social organizations is divided into two categories based on their registration, where the dissolution of social organizations that are not legal entities is carried out by the government, namely the Minister of Home Affairs. Meanwhile, for social organizations with legal entities, their dissolution is handed over to the Minister of Law and Human Rights.